2013
DOI: 10.1038/ijo.2012.215
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein receptor-related protein 1 variants and dietary fatty acids: meta-analysis of European origin and African American studies

Abstract: OBJECTIVE Low-density lipoprotein-related receptor protein 1 (LRP1) is a multi-functional endocytic receptor and signaling molecule that is expressed in adipose and the hypothalamus. Evidence for a role of LRP1 in adiposity is accumulating from animal and in vitro models, but data from human studies are limited. The study objectives were to evaluate (i) relationships between LRP1 genotype and anthropometric traits, and (ii) whether these relationships were modified by dietary fatty acids. DESIGN AND METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Scores of studies then reported statistically significant gene‐diet interactions between SNPs in candidate genes and macronutrient intake (saturated fat, carbohydrates, etc.) on plasma lipids, blood pressure, obesity and other cardiovascular phenotypes . However, there are hardly any studies that have analyzed the overall MedDiet pattern in these interactions, for instance, the effect on triglyceride levels of the interaction between the rs6950982 polymorphism near the SERPINE1 gene and adherence to MedDiet; and the effect on type 2 diabetes and obesity of the interaction between the FTO ‐rs9939609 and the MC4R ‐rs17782313 polymorphisms and MedDiet .…”
Section: Introductionmentioning
confidence: 99%
“…Scores of studies then reported statistically significant gene‐diet interactions between SNPs in candidate genes and macronutrient intake (saturated fat, carbohydrates, etc.) on plasma lipids, blood pressure, obesity and other cardiovascular phenotypes . However, there are hardly any studies that have analyzed the overall MedDiet pattern in these interactions, for instance, the effect on triglyceride levels of the interaction between the rs6950982 polymorphism near the SERPINE1 gene and adherence to MedDiet; and the effect on type 2 diabetes and obesity of the interaction between the FTO ‐rs9939609 and the MC4R ‐rs17782313 polymorphisms and MedDiet .…”
Section: Introductionmentioning
confidence: 99%